Team Dynamics In Emergency Surgery Teams: Results From A First International Survey - Lorenzo Cobianchi; Francesca Dal Mas; Maurizio Massaro; Paola Fugazzola; Federico Coccolini; Yoram Kluger; Ari Leppäniemi; Ernest E. Moore; Massimo Sartelli; Peter Angelos; Fausto Catena; Luca Ansaloni; et al. (World Society of Emergency Surgeons, 2024)
Indexed by WOS/SCOPUS